Belief dispersion and order submission strategies in the foreign exchange market - Ingrid Lo; Stephen Sapp (Bank of Canada, 2011)
This paper empirically examines how dispersions across investors beliefs influence traders order submission decisions in the foreign exchange market. Previous research has found that dispersion in traders beliefs regarding future macroeconomic announcements has a significant impact on both price dynamics and trading volume before the announcements in the foreign exchange and other financial markets. However, little is known about how this dispersion impacts traders choice in submitting different types of orders and thus to supply and demand liquidity either before or after such announcements. Since the types of orders submitted by traders at these times are the building blocks of the observed price and trading dynamics, it is important to understand how differences in investors' information sets before and after important macroeconomic announcements affect their order submission decisions. We find that (i) belief dispersion affects the size and aggressiveness of orders both before and after macroeconomic announcements, (ii) the magnitude of the impact of factors known to affect order choice depends on the level of belief dispersion, and (iii) the influence of information shocks (the revelation of unexpected information) on order choices depends on the level of belief dispersion.
Keywords: D4; G1; 330; Exchange rates; Market structure and pricing; Finanzmarkt; Devisenhandel; Finanzintermediär; Unvollkommene Information; Meinung; Ankündigungseffekt; Marktstruktur; Theorie